Biomechanical evaluation of cervical disc replacement with a novel prosthesis based on the physiological curvature of endplate - Lou, Jigang (J Orthop Surg Res, 2018)
BACKGROUND: Most of the current available cervical disc prostheses present a flat surface instead of an arcuate surface which is most similar to the morphology of cervical endplate. Therefore, we designed a novel prosthesis (Pretic-I, Trauson) based on the physiological curvature of the cervical endplate. Biomechanical evaluation of cervical disc replacement (CDR) with this novel prosthesis was performed and compared with the Prestige LP prosthesis. METHODS: Three motion segments of 18 cadaveric cervical specimens (C2-C7) were evaluated with a 75 N follower load. Overall, the biomechanics of three models, intact specimen, CDR with the novel prosthesis and CDR with the Prestige LP prosthesis, were studied to gain insight into the effective function of the novel prosthesis. The range of motion (ROM) of all three segments and intradiscal pressure (IDP) on adjacent levels were measured and analysed. RESULTS: Compared to the intact condition, the ROM of all three segments showed no significant difference in the replacement group. Moreover, there was also no significant difference in the ROM between the two prostheses. Besides, the IDP on the cranial adjacent level showed no obvious difference between the two prostheses; nevertheless, the IDP on the caudal adjacent level of the novel prosthesis was significantly less than the Prestige LP prosthesis. CONCLUSIONS: In summary, the novel disc prosthesis was effective to maintain the ROM at the target segment and adjacent segments. Besides, CDR with the novel prosthesis could reduce the IDP on the caudal adjacent level to a certain extent, compared with the Prestige LP prosthesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13018-018-0748-7) contains supplementary material, which is available to authorized users.